2021
DOI: 10.18632/oncotarget.27981
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic transformation of NIH/3T3 cells by the overexpression of L-type amino acid transporter 1, a promising anti-cancer target

Abstract: L-type amino acid transporter 1 (LAT1)/SLC7A5 is the first identified CD98 light chain disulfide linked to the CD98 heavy chain (CD98hc/SLC3A2). LAT1 transports large neutral amino acids, including leucine, which activates mTOR, and is highly expressed in human cancers. We investigated the oncogenicity of human LAT1 introduced to NIH/3T3 cells by retrovirus infection. NIH/3T3 cell lines stably expressing human native (164C) or mutant (164S) LAT1 (naLAT1/3T3 or muLAT1/3T3, respectively) were established. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Out of the investigated polymers, P­( O Bzl-Ser 23 - stat -Glu 67 ) revealed the ideal balance of Bzl and Glu. Although the BzlSer units are lipophilic, cationic building blocks, Glu provides the polymers with low-fouling properties, increased solubility in aqueous media, as well as cellular specificity mediated by transporter interactions, which are reduced in NIH 3T3 due to the absence of specific transporters. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the investigated polymers, P­( O Bzl-Ser 23 - stat -Glu 67 ) revealed the ideal balance of Bzl and Glu. Although the BzlSer units are lipophilic, cationic building blocks, Glu provides the polymers with low-fouling properties, increased solubility in aqueous media, as well as cellular specificity mediated by transporter interactions, which are reduced in NIH 3T3 due to the absence of specific transporters. , …”
Section: Resultsmentioning
confidence: 99%
“…Although the BzlSer units are lipophilic, cationic building blocks, Glu provides the polymers with lowfouling properties, increased solubility in aqueous media, as well as cellular specificity mediated by transporter interactions, which are reduced in NIH 3T3 due to the absence of specific transporters. 58,59 ■ CONCLUSIONS The synthesis of novel, zwitterionic Glu-functionalized polymers by RAFT polymerization was demonstrated. Defined polymers with protected side chains were prepared, Cy5labeled, and deprotected to yield tailored amino acidfunctionalized polymers.…”
Section: = Cell Growth Emission (Sample or Control) Emission (Blank)mentioning
confidence: 98%
“…Amino acid metabolism has been shown to participate in mTOR signaling ( 32 , 33 ). To detect whether mTOR signaling is involved in adipocyte and GS-induced chemoresistance of CRC to 5FU, we established co-culture models of adipocytes and CRC tumor cells using mouse adipocytes differentiated from 3T3-L1 cells AD co-cultured with mouse tumor cell lines B16, CT26, and MC38, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…CD98, also referred to solute carrier (SLC) 3A2, binds to six CD98lcs of the SLC7A amino acid transporter family (SLC7A5–7A8, 7A10, and 7A11) (Palacín et al, 2005). We produced mAb recognizing L‐type amino acid transporter 1 (LAT1)/SLC7A5 (Ohno et al, 2008; Ueda et al, 2019), and demonstrated the oncogenicity of LAT1 by the targeted disruption of the chicken LAT1 gene in DT40 cells (Ohkawa et al, 2011) and the oncogenic transformation of NIH3T3 cells through the overexpression of human LAT1 (Hayashi et al, 2021). We also produced α‐xCT/SLC7A11 mAb and identified xCT as a protein required for the maintenance of cancer stem cells (Ishimoto et al, 2011; Tsuchihashi et al, 2016; Yae et al, 2012).…”
Section: Introductionmentioning
confidence: 99%